Antigenic and Pathogenic Characteristics of QX-Type Avian Infectious Bronchitis Virus Strains Isolated in Southwestern China - Li, Shuyun (Viruses, 2019)
The QX-type avian infectious bronchitis virus (IBV) is still a prevalent genotype in Southwestern China. To analyze the antigenicity and pathogenicity characteristics of the dominant genotype strains (QX-type), S1 gene sequence analysis, virus cross-neutralization tests, and pathogenicity test of eight QX-type IBV isolates were conducted. Sequence analysis showed that the nucleotide homology between the eight strains was high, but distantly related to H120 and 4/91 vaccine strains. Cross-neutralization tests showed that all eight strains isolated from 2015 and 2017 belonged to the same serotype, but exhibited antigenic variations over time. The pathogenicity test of the five QX-type IBV isolates showed that only three strains, CK/CH/SC/DYW/16, CK/CH/SC/MS/17, and CK/CH/SC/GH/15, had a high mortality rate with strong respiratory and renal pathogenicity, whereas CK/CH/SC/PZ/17 and CK/CH/SC/DYYJ/17 caused only mild clinical symptoms and tissue lesions. Our results indicate that the prevalent QX-type IBVs displayed antigenic variations and pathogenicity difference. These findings may provide reference for research on the evolution of IBV and vaccine preparation of infectious bronchitis (IB).